2011
DOI: 10.1073/pnas.1105028108
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of lysine 120 of p53 endows DNA-binding specificity at effective physiological salt concentration

Abstract: Lys120 in the DNA-binding domain (DBD) of p53 becomes acetylated in response to DNA damage. But, the role and effects of acetylation are obscure. We prepared p53 specifically acetylated at Lys120, AcK120p53, by in vivo incorporation of acetylated lysine to study biophysical and structural consequences of acetylation that may shed light on its biological role. Acetylation had no affect on the overall crystal structure of the DBD at 1.9-Å resolution, but significantly altered the effects of salt concentration on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 50 publications
(64 reference statements)
5
87
0
Order By: Relevance
“…28,29 Acetylation of K120 alters the DNA binding specificity of p53, favoring its accumulation on low-affinity apoptotic gene promoters, such as bax and puma, triggering cell death. 28,29,46,47 We found that wild-type NIAM can promote p53 acetylation at K120. However, the N-terminal (NT) form lacks the ability to promote p53 acetylation despite retaining wild-type or greater abilities to bind Tip60, inhibit proliferation, and induce p53 transactivation of the p21 promoter.…”
Section: Discussionmentioning
confidence: 68%
“…28,29 Acetylation of K120 alters the DNA binding specificity of p53, favoring its accumulation on low-affinity apoptotic gene promoters, such as bax and puma, triggering cell death. 28,29,46,47 We found that wild-type NIAM can promote p53 acetylation at K120. However, the N-terminal (NT) form lacks the ability to promote p53 acetylation despite retaining wild-type or greater abilities to bind Tip60, inhibit proliferation, and induce p53 transactivation of the p21 promoter.…”
Section: Discussionmentioning
confidence: 68%
“…Acetylation at K120 is indispensable for activation of proapoptotic targets but is not required for activation of growth-arrest targets (16,17). Although the mechanism underlying this target specificity remains to be elucidated, it is possible that acetylation at K120 may impose specificity through altering the p53 quaternary structure and thus endowing p53 binding to low-affinity response elements that are found on proapoptotic promoters (29,30). We also noticed a small amount of cytoplasmic p53-p90 interaction.…”
Section: Discussionmentioning
confidence: 69%
“…In the case of p53, acetylation of Lys-120 by acetyltransferases of the MYST family has been shown to be important to distinguish between the apoptotic cell response and cell arrest (40,41). Moreover, biochemically, it has been demonstrated that Lys-120 is important for DNA binding and that its acetylation increases the DNA specificity of p53 (42)(43)(44). In the case of p73, Lys-138 (where we observed different conformations depending on the RE sequence) is the conserved equivalent residue of Lys-120 in p53.…”
Section: Discussionmentioning
confidence: 99%